2015
DOI: 10.1111/tri.12699
|View full text |Cite
|
Sign up to set email alerts
|

Lower tacrolimus trough levels are associated with subsequently higher acute rejection risk during the first 12 months after kidney transplantation

Abstract: SummaryThe premise that lower TAC trough levels are associated with subsequently higher first BPAR risk during the first 12 mo post-transplant was recently questioned. Using our prospectively followed cohort of 528 adult, primary kidney transplant recipients (pooled across four randomized trials) who received reduced TAC dosing plus an IMPDH inhibitor, TAC trough levels measured at seven time points, 7, 14 days, 1, 2, 3, 6 and 9 months post-transplant, were utilized along with Cox's model to determine the mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 30 publications
11
46
0
1
Order By: Relevance
“…This is in accordance with recently published data by Gaynor et al, 16 suggesting that trough levels <4 ng/mL should be avoided. This is in accordance with recently published data by Gaynor et al, 16 suggesting that trough levels <4 ng/mL should be avoided.…”
Section: C/d Ratio (Ng/ml/mg) Variationsupporting
confidence: 93%
“…This is in accordance with recently published data by Gaynor et al, 16 suggesting that trough levels <4 ng/mL should be avoided. This is in accordance with recently published data by Gaynor et al, 16 suggesting that trough levels <4 ng/mL should be avoided.…”
Section: C/d Ratio (Ng/ml/mg) Variationsupporting
confidence: 93%
“…However, when we delineated mean TAC C 0 into different ranges, we found that patients with a mean TAC C 0 of 0 – 3.9 ng/ml and 4 – 5.9 ng/ml had a higher risk of T-cell mediated rejection compared to patients with a mean TAC C 0 of ≥ 8 mg/ml. This finding may be supported by other retrospective reports (32) as well as Gatault et al, as their control group achieved a TAC C 0 of 7.4 ng/ml with 3 episodes of T-cell mediated rejection at 12 months and the intervention group achieved a TAC C 0 of 5.6 ng/ml with 11 episodes of rejection (p=0.016) at 12 months.…”
Section: Discussionsupporting
confidence: 79%
“…[106] The lower exposure to Tac following standard dosing may be responsible for the higher acute rejection risk after kidney transplantation in recipients of African descent. [112] By contrast, CYP3A5 genotype appears not to be a risk factor for the poorer long-term kidney allograft survival observed in patients of African descent, despite its well-characterized influence on Tac dose requirement. [113] In addition to CYP3A5*3, the CYP3A5*6 and CYP3A5*7 variant alleles can also lead to the absence of functional CYP3A5 protein.…”
Section: Ethnic Considerationsmentioning
confidence: 96%